ANALISIS SISTEM KELEMBAGAAN DALAM PERENCANAAN DAN STRATEGI PENGELOLAAN LAHAN KRITIS DAS BILA - Andi Nuddin; Naik Sinukaban; Kukuh Murtilaksono; Hadi S. Alikodra (Jurnal Penyuluhan, 2007)
The rehabilitation program of critical land had been done since 1985 until 2001, but Bila watershed condition did not get better, even the width of critical land and erotion got more increase. Those were caused by some factors, involved: unaccruracy of technology, limited baudget, and unoptimal institution. Analysis of this study was focused on institution factor. Some of institution aspects that caused failure of rehabilitation of critical land Bila watershed, were is: role of institution sector, performance of management function, weakness on coordination, unrelevant of strategic program, and priority activity. Data collected was conducted by survey on some samples. Interpretative Structural Modelling and Analitycal Hierarchy Process were applied and the result shown that: (1) The main subject in critical land Bila watershed management were institution at regency level, which is Bappeda and Bapedalda, (2) unsuccess of rehabilitation of critical land Bila watershed was caused by planning weakness, (3) top-down policy, one of nine from main factors must be handled for effectiveness of coordination function, (4) to equalize vision and mission Bila watershed management cross territory was one of foor priority strategic frogram in critical land Bila watershed management, (5) and to increase knowledge and farmer skills were one of seven priority activity in critical land Bila watershed management.